(untitled) (REMUNOM, 2024)
Objective: Construction of a chatbot that directs patients to the dental clinics of FO-UFPA, according to your symptons. Methods: This is a development study, which in your elaboration, went through stages such as: semi-structured interviews, construction of content and scenarios of the chatbot and settings. Results: The developed technology initiates the interaction from a primary user greeting, explains how it works and continues with questions that will direct the patient to the clinic best suited to their demand. Conclusion: The tool seeks to help servers and patients at the time of referral, indicating the possible clinic where the user will receive care, reducing the wait for the start of dental treatment